Successful Allogeneic Hematopoietic Stem Cell Transplantation from A 5/10 Mismatched Unrelated Donor in A Patient with Donor-Specific Anti-HLA Antibodies. - Moreno, A; Suárez-Lledó, M; Almeida, S; Fernández-Avilés, F; Gutiérrez-García, G; Martínez, C; Rosiñol, L; Solano, MT; Serra, C; Cid, J; Lozano, M; Marín, P; et al. (Journal of Hematology and Oncology Research, 2018)
Hematopoietic stem cell transplantation (HSCT) from a mismatched unrelated donor, an haploidentical donor or a cord blood unit (CBU) has become a widely aviable approach if patient lacks a matched related or unrelated donor. However, if the patient has anti-HLA antibodies against antigens present in the mismatched donor or CBU (donor-specific antibodies, DSAs) this option should be disregarded due to the high risk of graft failure. Desensitization can be used to reduce levels of DSAs but this technique has limited results. We report the case of a 62-year-old woman with DSAs against two haploidentical familiar donors who failed desensitization of DSAs. Finally she underwent a HSCT from a 5/10 mismatched unrelated donor which has been successful.
Keywords: Mismatched unrelated stem cell transplantation; graft failure; high dose posttransplant cyclophosphamide; donor-specific antibodies (DSAs)